2022
DOI: 10.1039/d2ma00232a
|View full text |Cite
|
Sign up to set email alerts
|

A novel ion-responsive photonic hydrogel sensor for portable visual detection and timely removal of lead ions in water

Abstract: Lead ion (Pb2+) contamination is a worldwide serious environment problem. Although various methods have been developed for detection or removal of Pb2+ in water environment, possessing both highly-selective, visual monitoring...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Pb 2+ adsorption onto the MCNC occurs mainly on the heterogeneous surface or surface support positions with different affinities. The Freundlich constant n is larger than 1, indicating the high adsorption intensity of the MCNC toward Pb 2+ [12]. This is a multilayer adsorbent material.…”
Section: Effect Of the Initial Concentration Of Pb 2+ On The Adsorpti...mentioning
confidence: 95%
“…Pb 2+ adsorption onto the MCNC occurs mainly on the heterogeneous surface or surface support positions with different affinities. The Freundlich constant n is larger than 1, indicating the high adsorption intensity of the MCNC toward Pb 2+ [12]. This is a multilayer adsorbent material.…”
Section: Effect Of the Initial Concentration Of Pb 2+ On The Adsorpti...mentioning
confidence: 95%
“…[88] Cheng et al reported an ion-responsive photonic hydrogel sensor for visual detection. [89] The 18-crown-6 unit in the hydrogel backbone acts as a Pb 2+ -responsive acceptor and forms a host-guest inclusion complex with Pb 2+ in water. In this case, the hydrogel undergoes a hydrophobic to hydrophilic transition and gradually absorbs water and swells, which causes an increase in the lattice spacing of embedded Fe 3 O 4 CNCs and a gradual red shift of the structural color (Figure 19a).…”
Section: Sensorsmentioning
confidence: 99%
“…The significant advantages of RPCHs with a non-fading nature, high stability, and bright colors make them applicable as colorimetric detection devices. Through the development of an ion-responsive photonic hydrogel sensor composed of poly­( N -isopropylacrylamide- co -benzo-18-crown-6-acrylamide), Shen et al achieved the colorimetric detection of Pb 2+ manually . Additionally, the linear detection of Cu­(II) ions was achieved by using carbon dot-based inverse opal hydrogels with photoluminescence to achieve the dual-mode detection of solvents and metal ions .…”
Section: Introductionmentioning
confidence: 99%